Adsorption of Ni(II), Cd(II) from Aqueous Single Metal Solutions by the Palm Thread Impregnated with Sodium Dodecyl Benzene Sulfonate - Lv, Wengang; Zhou, Yanbo; He, Bing; Qiu, Haibing; Lu, Jun (Asian Journal of Chemistry, 2012)
Adsorption of Ni(II) and Cd(II) from aqueous solutions was searched by using palm threads (PT) impregnated with anionic surfactant sodium dodecyl benzene sulfonate (SDBS). Two types of palm threads were used/applied; one was untreated palm threads (UPT) and the other was basified with NaOH i.e., basified palm threads (BPT). When treated with surfactant-impregnated basified palm threads (SDBS-BPT) the removal of Ni(II) and Cd(II) was up to 21.0 and 25.3 mg g-1, which was more better than the Ni(II) and Cd(II) removal performance of untreated palm threads with surfactant (SDBS-UPT) (i.e., 9.2 and 16.6 mg g-1). The kinetics of the adsorption of Ni(II) and Cd(II) onto the surfactant-impregnated palm threads were best described by the pseudo-second-order model and after being pretreated with NaOH. The sorption rate constants (k2) of Ni(II) and Cd(II) increased from 0.5499 and 0.2017-1.5023 and 0.7274 g mg-1 h-1, respectively and the total basicity also increased from 310.5-530.8 μeq g-1. The isotherm was described better by the Freundlich adsorption isotherm than by the Langmuir model. The active groups and the total basicity enhanced significantly. when it was pretreated with NaOH and impregnated with SDBS, which resulted in the improved sorption rate and sorption capacity for Ni(II) and Cd(II). The sorption performance of SDBS-BPT indicates that it is an effective biosorbent for removing heavy metals from aqueous solutions.